Estudio a nanoescala de las interacciones entre liposomas recubiertos con biopolimeros y superficies sólidas de biomateriales - Ramos, G. (2010)
The study is based on finding an explanation for the opposite behavior observed at the interface between hard and soft materials, specifically on biological systems, like liposomes, when they interact with inorganic surfaces of biomaterials, such as silica, aluminum, mica, ceramics and titanium. The purpose is to analyze the relationships between surface ionic equilibria, attractive forces between liposome-surface/degree of deformation and changes in the surface properties of adsorbed liposome nanoparticles, via surface modification of liposomes with biopolymers, such as chitosan. Progress was made in the understanding of the dynamics of the interfaces of different consistency, using lipid vesicles as a model and found that biopolymer coating of lipid vesicles with chitosan, provides a better physical stability and an increase on interface biomimetics between nanoparticle-inorganic biomaterial. These results constitute the first step to understanding actual interactions between biological microparticles that usually circulate in the blood and the surfaces of implants or biomaterials, which are associated with subsequent rejection reactions originated by immunological processes generated by interface incompatibilities.